Genetic diversity and population structure of long-tailed macaque (Macaca fascicularis ) populations in Peninsular Malaysia - Nikzad, Sonia; Tan, Soon Guan; Yong Seok Yien, Christina; Ng, Jillian; Alitheen, Noorjahan Banu; Khan, Razib; Rovie-Ryan, Jeffrine J.; Valdiani, Alireza; Khajeaian, Parastoo; Kanthaswamy, Sree (John Wiley & Sons Ltd, 2014)
Background The genetic diversity and structure of long-tailed macaques (Macaca fascicularis) in Peninsular Malaysia, a widely used non-human primate species in biomedical research, have not been thoroughly characterized.